2017
DOI: 10.3892/ijo.2017.3929
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of tumor protein D (TPD) 52 and TPD54 on oral squamous cell carcinoma cells

Abstract: The tumor protein D52 (TPD52) protein family includes TPD52, -53, -54 and -55. Several reports have shown important roles for TPD52 and TPD53, and have also suggested the potential involvement of TPD54, in D52-family physiological effects. Therefore, we performed detailed expression analysis of TPD52 family proteins in oral squamous cell carcinoma (OSCC). Towards this end, TPD54-overexpressing or knocked-down cells were constructed using OSCC-derived SAS, HSC2 and HSC3 cells. tpd52 or tpd53 was expressed or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Studies are limited with regard to the biological function of TPD54 in cancer cells, especially in breast cancer. In oral squamous cell carcinoma cells, TPD54 was reported to be a negative regulator of tumor progression by downregulating anchorage-independent cell growth and migration in vitro and by attenuating tumor growth in vivo [12]. Our data demonstrate that, in breast cancer cells, downregulation of TPD54 can reduce cellular oxygen consumption, increase colony formation, and decrease cancer cell sensitivity to metformin treatment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Studies are limited with regard to the biological function of TPD54 in cancer cells, especially in breast cancer. In oral squamous cell carcinoma cells, TPD54 was reported to be a negative regulator of tumor progression by downregulating anchorage-independent cell growth and migration in vitro and by attenuating tumor growth in vivo [12]. Our data demonstrate that, in breast cancer cells, downregulation of TPD54 can reduce cellular oxygen consumption, increase colony formation, and decrease cancer cell sensitivity to metformin treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies have also shown that TPD54 affects cell proliferation, cell adhesion, and invasion [11]. Furthermore, TPD54 has been shown to have opposite effects to TPD52 in oral squamous cell carcinoma (OSCC) by preventing colony formation and cell migration [12]. However, the underlying mechanisms of TPD54’s role in cancer, including breast cancer, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al [21] showed that the expression of PC-1/PrLZ, a splicing variant of human TPD52, is increased by stress from irradiation. Moreover, we revealed that TPD52 is strongly expressed at the center of OSCC tissue and plays an important role in OSCC cell growth [19]. Another report of ours represented that TPD52 is post-transcriptionally regulated by T-cell intercellular antigen (TIA) 1 and TIA-related protein (TIAR) via mRNA stability [22].…”
Section: Introductionmentioning
confidence: 57%
“…Resected specimens were xed with 10% formalin, embedded in para n, stained with hematoxylin and eosin (H-E) (Sakura Finetek Japan, Tokyo, Japan), and then immunohistochemically stained for p62, Akt, and phospho-Akt, as described previously [19].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation